Optimizing the Aerodynamic Performance of a Duct–Rotor System for Drones: A Comprehensive Study on the Coupled Parameters - Wei Wei; Shiyi Wei; Zhifang Ke; Meng Guo; Yongjie Shu; Qingkai Meng; Leilei Jia; Maofeng Zhang; Shurui Han (Drones)
The integrated ducted structure significantly enhances the aerodynamic performance of the duct–rotor system, reducing noise and enhancing rotor safety. However, in the duct–rotor system, the coupled parameters of the rotor and the duct are crucial to its aerodynamic characteristics. This study employs a Computational Fluid Dynamics numerical analysis to investigate the aerodynamic performance of the duct–rotor, focusing on coupled parameters related to the rotor blade’s relative position and tip gap. Additionally, our research delves into the fundamental mechanisms of key coupled parameters, such as the blade tip gap, elucidating their role in optimizing the duct–rotor’s aerodynamics. The results emphasize the critical role of the tip gap in influencing the aerodynamic performance of the duct–rotor. Notably, when the tip gap exceeds 3.0% of the duct’s radius, the aerodynamic advantage provided by the duct is insufficient to offset the loss in the rotor’s performance. As the tip gap exceeds 7.0% of the duct’s radius, the aerodynamic deterioration caused by the duct gradually stabilizes. Furthermore, the influence of rotor blade position on aerodynamic performance is relatively minor. However, placing the rotor at the duct exit position proves advantageous for improving the aerodynamic distribution characteristics of the system.